Do National Ecological Civilization Pilot Zones improve public environmental satisfaction? Evidence from China - Dong, Yukai; Qin, Shida; Li, Yuhong (Frontiers in Environmental Science, 2025)
Existing studies on the effectiveness of the National Ecological Civilization Pilot Zones (NECPZs) have largely concentrated on objective outcomes such as green innovation and ecological efficiency, while paying limited attention to public environmental satisfaction, which represents a critical subjective indicator of governance performance. This study draws on multi-year data from the Chinese Social Survey and employs a staggered difference-in-differences model to systematically assess the impact of NECPZs on public environmental satisfaction in pilot provinces and to uncover the underlying mechanisms. The results show that the implementation of NECPZs significantly enhances public environmental satisfaction. This effect operates primarily through two channels: improving air quality and fostering public participation in environmental governance. Moreover, the heterogeneity analysis indicates that the positive effect of NECPZs on public environmental satisfaction is more pronounced among individuals who use the internet more frequently, likely because they are better able to access environmental information and perceive policy improvements. In contrast to previous studies that highlight the amplifying effect of Internet-based media on public environmental dissatisfaction, this study demonstrates its positive effect on public environmental satisfaction. This study offers practical implications for policymakers, highlighting that greater transparency, stronger information disclosure, and broader citizen participation are crucial for enhancing public environmental satisfaction and ensuring the long-term legitimacy and sustainability of ecological policies.